2018
DOI: 10.5935/abc.20180053
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Attenuates Sympathetic Activity and Improves Morphometry of Splenic Arterioles in Spontaneously Hipertensive Rats

Abstract: BackgroundAlterations in the structure of resistance vessels contribute to elevated systemic vascular resistance in hypertension and are linked to sympathetic hyperactivity and related lesions in target organs.ObjectiveTo assess the effects of exercise training on hemodynamic and autonomic parameters, as well as splenic arteriolar damages in male Wistar Kyoto (WKY) and Spontaneously Hypertensive Rats (SHR).MethodsNormotensive sedentary (WKYS) and trained (WKYT) rats, and hypertensive sedentary (SHRS) and train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
3
9
0
1
Order By: Relevance
“…In our study, rest HR reduction after training suggests involvement of sympathetic activity in hypotensive effect mitigation (20). Indeed, MAP of SHR-T rats was still higher than normotensive rats despite a decrease of values compared with SHR-C, but many other studies with different types of physical exercise have shown the same results (29,32,38,39,62). We also observed an increase in the left ventricular weight/BW ratio in hypertensive rats, especially when they were trained.…”
Section: Discussionsupporting
confidence: 72%
“…In our study, rest HR reduction after training suggests involvement of sympathetic activity in hypotensive effect mitigation (20). Indeed, MAP of SHR-T rats was still higher than normotensive rats despite a decrease of values compared with SHR-C, but many other studies with different types of physical exercise have shown the same results (29,32,38,39,62). We also observed an increase in the left ventricular weight/BW ratio in hypertensive rats, especially when they were trained.…”
Section: Discussionsupporting
confidence: 72%
“…Many considerable evidences support the therapeutic and protective effects of exercise on the body, including improvement of insulin sensitivity of diabetic mice, attenuating sympathetic activity, arterial pressure, and heart rate in the spontaneously hypertensive rats [24]. Mitochondrial biogenic response, components of the electron transport chain, mtDNA, and related lipid metabolic pathways are all increased after exercise training [25].…”
Section: Mechanisms Of Action For Physical Exercisementioning
confidence: 99%
“…DNA is oxidized by ROS to form 8-oxo-dG which can be detected in plasma and urine [94]. AngII-induced insulin resistance is relevant to ROS, which can impair insulin signaling by decreasing phosphorylation of IRS1 and Akt and translocation of GLUT4 to the plasma membrane [24].…”
Section: Mechanisms Of Action For Physical Exercisementioning
confidence: 99%
“…In the literature, SHR rats have been found to present augmented sympathetic activity in the kidney at around 4-5 months old (16) and in the spleen at around 13-20 weeks old (8). In the heart, 45-50-week male SHR rats present higher sympathetic effect and sympathovagal index, followed by reduced parasympathetic effect, compared to control rats (17). However, when the cardiac sympathetic tone of 4-6-month-old SHR rats was evaluated by spectral analysis, no difference was found compared to Wistar rats, while the cardiac parasympathetic tone was reduced in SHR (18).…”
Section: Discussionmentioning
confidence: 98%